MODAL PSIKOLOGIS, KONFLIK PERAN GANDA, DUKUNGAN KELUARGA TERHADAP KESEIMBANGAN KEHIDUPAN KERJA PADA PEGAWAI WANITA DI KANTOR PEMERINTAH KOTA BEKASI - Novita Dian Iva Prestiana; Rony Setiawan (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2021)
This study aims to determine the characteristic of self efficacy, reciliency, optimism, self esteem, work family conflict, family support, and work-life Balance. The type of data used in this study is quantitative design. The sample used in this study were cluster random sampling technique on 300 woman employees at Bekasi Government.. The data collection tool used was self efficacy, reciliency, optimism, self esteem, work family conflict, family support, and worklife Balance. The data analysis technique used correlation and multistage regression. The results showed self efficacy had a positive significant correlation with work-life balance, reciliency had a positive significant correlation with work-life balance, optimism had a positive significant correlation with work-life balance, self esteem had a positive significant correlation with work-life balance, work-family conflict had a negative significant correlation with worklife balance, family support had a positive significant correlation with work-life balance. Multistage regression found that self efficacy, reciliency, optimism, self esteem, work family conflict, and family support had a significant effect on work-life balance.